Association of OPRM1, MIR23B, and MIR107 genetic variability with acute pain, chronic pain and adverse effects after postoperative tramadol and paracetamol treatment in breast cancer - Vidic Zala; Goricar Katja; Strazisar Branka; Besic Nikola; Dolzan Vita (Radiology and Oncology, 2023)
Tramadol is an opioid analgesic often used for pain management after breast cancer surgery. Its analgesic activity is due to the activation of the μ-opioid receptor, encoded by the OPRM1 gene. This study investigated the association of genetic variability in OPRM1 and its regulatory miRNA genes with outcomes of tramadol/paracetamol treatment after breast cancer surgery with axillary lymphadenectomy.